PRINSIP-PRINSIP PERENCANAAN PENDIDIKAN DALAM PERSPEKTIF AL-QUR’AN - Suja'i, Ahmad (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2018)
Management experts have agreed to put planning as the main function and even become the base for the remain other management functions. Planning is a very basic matter for organizations, including educational institutions. In order to make good planning, several planning principles are needed which must be used as a guide. The principle of conventional education planning includes interdisciplinary principles, flexible principles, principles of efficiency-effectiveness, principles of progress of change, principles of objective, rational and systematic, cooperative-comprehensive principles and principles of human resources development. In this article the author tries to describe the planning principles in the perspective of the Qur'an. (1) Interdisciplinary principles (Bayna Huqul Al-Dirosah), QS. An-Nahl [16]: 89, (2) Flexible principle, QS. Al-Hajj [22]: 78, (3) (4) The principle of effectiveness-efficiency (Fu’aliyah-kafaah), QS. Al-Kahf [18]: 103-104, (5) The principle of the progress of change (Taqaddum At-Taghyiir), QS. Al-Hajj [22]: 77, (6), Objective, rational and systematic principle (Maudhu'i, ‘Aqly and Muntadhimun), QS. Al-Baqarah [2]: 216, (7) Cooperative-comprehensive principle, QS. Al-Maidah [5]: 2, and (8) Principles of human resources development, QS. Al-Kahfi [18]: 2.